Determinants of the Quality of Village Government Financial Statements - Jatmiko, Bambang; Utami, Tiyas Puji; Nugroho, Ardiansyah Wahyu (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study examines the effect of information technology, transparency, human resource competence, and internal control systems on the quality of financial reports. It looks at the effect of accountability variables as intervening variables on human resource competencies and internal control systems. The problem under study is that there are still many cases of budget misappropriation caused by the poor quality of financial reports in the village government of Gunungkidul Regency. The type of research data is primary data obtained by distributing questionnaires. This study received a sample of 204 respondents in 144 villages and was selected by purposive sampling method aimed at village officials, namely the village head, village secretary, and village treasurer. The results of this study indicate that Utilization of information technology, Transparency, Human Resource Competency, and Accountability positively affect the quality of financial reports on village governments. Meanwhile, the internal control system cannot improve the quality of financial reports. Practically, this study provides input to the central government and village governments to improve related factors that can improve the quality of financial statements.